1995
DOI: 10.1007/bf00315786
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a protein which binds specifically to the upstream region of the pcbAB gene in Penicillium chrysogenum

Abstract: The upstream region of the pcbAB gene from Penicillium chrysogenum was screened for protein-binding sites using an electromobility shift assay. A specific protein/DNA interaction was detected within a fragment covering the region -387 to -242 relative to the pcbAB translational start codon. The appearance of this protein and pcbAB mRNA in culture extracts occurred at the same time point in fermentations, suggesting that the protein might be a transcription activator. The putative upstream activating sequence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…chrysogenum by band-shift assays. Chu et al (1995) and Feng et al (1995) reported independently of each other that partially purified crude extracts of f? chrysogenum bound in vitro to the sequences TGCCAAG and GCCAAGCC, respectively.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…chrysogenum by band-shift assays. Chu et al (1995) and Feng et al (1995) reported independently of each other that partially purified crude extracts of f? chrysogenum bound in vitro to the sequences TGCCAAG and GCCAAGCC, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, it has become evident that at the molecular level, regulation of penicillin biosynthesis is complex. Several protein factors seem to be involved (Brakhage and Van den Brulle, 1995;Chu et al, 1995;Feng et al, 1995;Haas and Marzluf, 1995; P6rez-Esteban et al, 1995;Tilburn et al, 1995;Then Bergh et al, 1996).For the studies presented here, A. nidu1an.s was used because this fungus has, in contrast to the deuteromycete P chrysogenum which is employed for industrial production of penicillin, a welldefined sexual cycle facilitating genetic analyses (MacDonald and Holt, 1976;Timberlake and Marshall, 1988;Davis and Hynes, 1989; Clutterbuck, 1993).The A. nidulans nut @enDE) gene lies downstream of the ipnA gene, separated by an intergenic region of 825 bp (Ramon et al, 1987;Montenegro et al, 1990;Tobin et al, 1990; Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chu et al (17) and Feng et al (23) reported independently that partially purified crude extracts of P. chrysogenum bound in vitro to the sequences TGCCAAG and GCCAAGCC, respectively, which appear to be similar to the PACC binding sites identified in A. nidulans (54). Haas and Marzluf (24) observed that the nitrogen regulatory protein NRE of P. chrysogenum bound to GATA-containing sequences in the intergenic region in vitro.…”
mentioning
confidence: 87%
“…Chu et al (17) showed that proteins in partially purified extracts recognize the TGCCAAG sequence. In parallel, Feng et al (29) reported a nuclear factor (NF-A) that recognizes a slightly different binding sequence, GCCAAGCC.…”
Section: Protein Binding Sites In the Upstream Region Of The Penicillmentioning
confidence: 99%